Pengaruh Citra Merek, Gaya Hidup, Kualitas Produk, Brand Ambassador dan Getok Tular Terhadap Minat Beli Produk Smartphone Merek Samsung di Daerah Istimewa Yogyakarta - Sudaryana, Arif; Rizal Faihaan, Ahmad; Susilowati, Fitri (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This research aims to understand the impact of consumer behavior, lifestyle, product quality, brand ambassadors, and brand awareness on consumers' desire to purchase Samsung smartphones. The sample population for this study is the Yogyakarta Istimewa people who have used or are currently using Samsung pen drives. Sampling technique is used to collect data, and kuisoner is used as a tool to collect data with 120 respondents. The nature of this research is qualitative. Every study shows that real estate brokers, lifestyle bloggers, brand ambassadors, and product quality specialists all have a favorable and substantial impact on consumers' decisions to buy Samsung devices. The variable that reflects the percentage of smartphone purchases that are between 70.7% and 29.3% can be well explained by factors like lifestyle, brand ambassadorship, product quality, and tularity. This variable is explained by other variables that were not included in this study.